The gamma-ray sky seen at X-ray energies. I. Searching for the connection between X-ray and gamma-rays in Fermi BL Lac objects - Marchesini, Ezequiel Joaquín (2019)
Context. BL Lac objects are an extreme type of active galactic nuclei (AGNs) that belong to the largest population of γ-ray sources: blazars. This class of AGNs shows a double-bumped spectral energy distribution that is commonly described in terms of a synchrotron self-Compton (SSC) emission process, whereas the low-energy component that dominates their emission between the infrared and the X-ray band is tightly connected to the high-energy component that peaks in the γ-rays. Two strong connections that link radio and mid-infrared emission of blazars to the emission in the γ-ray band are well established. They constitute the basis for associating γ-ray sources with their low-energy counterparts.Aims. We searched for a possible link between X-ray and γ-ray emissions for the subclass of BL Lacs using all archival Swift/XRT observations combined with Fermi data for a selected sample of 351 sources.Methods. Analyzing ∼2400 ks of Swift/XRT observations that were carried out until December 2018, we discovered that above the γ-ray flux threshold Fγ ≈ 3 × 10−12 erg cm−2 s−1 , 96% of all Fermi BL Lacs have an X-ray counterpart that is detected with signal-to-noise ratio higher than 3.Results. We did not find any correlation or clear trend between X-ray and γ-ray fluxes and/or spectral shapes, but we discovered a correlation between the X-ray flux and the mid-infrared color. Finally, we discuss on a possible interpretation of our results in the SSC framework.